2018
DOI: 10.1104/pp.18.00257
|View full text |Cite
|
Sign up to set email alerts
|

SMALL AUXIN UP RNA62/75 Are Required for the Translation of Transcripts Essential for Pollen Tube Growth

Abstract: Seeds or grains constitute the major source of food supply around the world, and their production depends on successful pollination, double fertilization, and subsequent embryogenesis. The pollen tube, the reduced male gametophyte of flowering plants, travels through the transmitting tract inside female tissues and delivers the male gametes (two sperm cells) to fertilize female gametes (egg and central cell) for double fertilization (Berger et al., 2008). Well-programmed microspore development, pollen germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…Indeed, heat stress inhibits elongation of the pollen tube into the ovary by impairing auxin homeostasis in pollinated pistils, which results in sterile spikelets [33]. However, in this study, auxin might not be the determining factor in this process, although this hormone plays a key role in pollen tube elongation in plants [3437]. The highest auxin level was found in plants treated with sucrose at 5 DAF, while no significant difference was found between the control and sucrose plus ABA treatment (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, heat stress inhibits elongation of the pollen tube into the ovary by impairing auxin homeostasis in pollinated pistils, which results in sterile spikelets [33]. However, in this study, auxin might not be the determining factor in this process, although this hormone plays a key role in pollen tube elongation in plants [3437]. The highest auxin level was found in plants treated with sucrose at 5 DAF, while no significant difference was found between the control and sucrose plus ABA treatment (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…SAUR19 directly interacts with D-clade type 2C protein phosphatases (PP2C-D) to promote cell expansion by enhancing activity of plasma membrane (PM) H + -ATPase (Spartz et al, 2014). Some other Arabidopsis SAUR genes are implicated in plant growth and development regulation (Ren & Gray, 2015;He et al, 2018). Although the majority of SAUR genes that have been studied are positive regulators of plant growth (Chae et al, 2012;Spartz et al, 2012;Kong et al, 2013;Li et al, 2015), negative regulation has also been suggested for a few SAURs (Hou et al, 2013;Markakis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin and brassinosteroid (BR) are two major classes of hormone, which are considered as master regulators in different plant development processes and response to various biotic and abiotic stresses [ 43 , 44 ]. In addition, the role of auxin and BR and their binding proteins is well-known in anther development, pollen tube growth, and subsequent fertilization [ 45 ]. There was a significant difference in DEGs related to auxins, BR and abscisic acid metabolism, which corroborates with previous findings, stating that plants employ the iterative trade-off to modulate differential organ growth upon the elicitation of immune response [ 46 ].…”
Section: Discussionmentioning
confidence: 99%